Quick Homework Help

2x + y - z = 0 x - y + z = 6 x + 2y + z = 3 ⚑ Flag

by Caleb086 at March 09, 2011

Hey there, there is a problem on it.i think it is not correct Question.1)-2(x-y+z)=-2x+2y-2z=6----->2y=2x+2z+62)x+2y+z=3-------> 2y=3-x-zso that, from point 1&2, we have:2x+2z+6=3-x-z  SO  3+3z+3x=0  SO  x+z=-1and also we know that: x+2y+z=3so it is equal by 2y-1=3 so that y=2but we have x-y+z=6 , but here is a problem:x+z=-1 & y=2 ------> -1-2≠6I THINK IT IS INCORRECT QUESTION

darklight March 10, 2011

OH,OH,OH. Sorry, the question is exactly right, i made a mistake in my solve.It is my new solve:-2(x-y+z)=-12----> -2x+2y-2z=-12 so that: 2y=2x+2z-12and also we have: 2y+x+z=3 so thet:2y=3-x-zAs you know, we have: 2x+2z-12=3-x-z So that:3x+3z=15------> x+y=5we have x+z+2y=3, so: 2y=-2, so y = -12x+(-1)-z=0------> 2x-z=1                               x+z=5   so we have x=2we have 2+2(-1)+z=3---------->  z=3excuse me for my last rong solvement

darklight March 11, 2011

i think it is not correct Question.1)-2(x-y+z)=-2x+2y-2z=6----->2y=2x+2z+62)x+2y+z=3-------> 2y=3-x-zso that, from point 1&2, we have:2x+2z+6=3-x-z SO 3+3z+3x=0 SO x+z=-1and also we know that: x+2y+z=3so it is equal by 2y-1=3 so that y=2but we have x-y+z=6 , but here is a problem:x+z=-1 & y=2 ------> -1-2≠6

baseball March 12, 2011

This is just a system of equations right?I think you can solve this problem using the elimination method pretty easily.2x + y - z = 0  x - y + z = 6When you add these equations together, you get x = 6.There, you have the x-value! Hope you can solve it from here, it just takes a little bit of substitution and thinking

Gentou March 15, 2011